Current and Emerging Pharmacotherapies for Zika Virus: A Comprehensive Review - Queeny Wilcy Noronha,; Thanshifa Fathima,; Bhat, Ramdas; A R Shabaraya, (Indian Journal of Pharmacy & Drug Studies, 2023)
Zika virus is a single-stranded RNA virus that belongs to the Flaviviridae family and was first identified in the Zika Forest of Uganda in 1947. Since 2007, there have been several outbreaks of Zika virus in various countries, with the most significant outbreak occurring in Brazil in 2015. The virus is primarily transmitted by infected Aedes mosquitoes, but it can also be sexually transmitted, transmitted through blood transfusions, and from mother to child during pregnancy. While most people who become infected with Zika virus experience mild or no symptoms, there is a potential for severe outcomes, including neurological complications like Guillain-Barre syndrome and congenital birth defects like microcephaly. This article provides an overview of Zika virus, its transmission, symptoms, and potential impacts on public health. Despite no specific antiviral treatment available for Zika virus, there are ongoing efforts to develop vaccines and treatments. The potential for sexual transmission of Zika virus has also led to recommendations for safe sexual practices, particularly for pregnant women or women who may become pregnant. Continued research is needed to better understand the virus and its potential impacts on public health, including long-term effects and the potential for the virus to be transmitted through other routes. The emergence of Zika virus as a significant public health concern highlights the need for continued vigilance and research to mitigate the potential impacts of this and other emerging infectious diseases. Given the threat of Zika virus and its ability to spread across international borders, global collaboration and coordinated responses are essential to address emerging infectious disease threats. It is essential to continue investing in research and development to reduce the impact of emerging infectious diseases on public health.